The threat of lingua globalization towards vernaculars in South Sulawesi - Ramli, Ramli; Setyawan, Farid Helmi; Rampeng, Rampeng (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
Indonesia seems to face the crisis of local language, especially in urbanization. The emergence of English as a lingua franca is undeniable to decrease the existence of vernaculars. The research aims to reveal the reason for urbanization giving the biggest impact on the Indonesian’s local language in South Sulawesi and how to maintain the use of local language is facing extinction in this century. This study applied a descriptive qualitative design by interviewing three subjects. They are lecturers and students. The interview result showed that globalization is one of the plagues that had the impact on vernaculars becoming threatened in this present day, influenced people to obey their vernaculars, and also affected the youths’ psychological order and their perception. It is due to the significant use of international or national language and the less effort from the government in maintaining the vernaculars, particularly in South Sulawesi. One suggestion can be proposed that local content needs to be involved in the Education sector e.g., intensifying vernacular use in school and family, and sustainably promoting cultural heritage to attract the society.